Power Dense High-Speed Motor-Generator System for Powering Futuristic Unmanned Aircraft System (UAS) - Rahman, Syed; Hasanpour, Shima; Khan, Irfan; Toliyat, Hamid A.; Hussain, Hussain A. (IECON 2022 – 48th Annual Conference of the IEEE Industrial Electronics Society, 2022)
Unmanned aircraft systems (UAS) have emerged as a useful aid for entertainment, monitoring, and defense activities. A Significant research effort is being invested in UASs to increase the payload capacity and monitoring/processing capabilities. To achieve this, the power density of UAS must be increased. In conventional UAS, for starting the fuel-powered engine, an engine starter is usually used. Once the engine starts, the engine torque is used for driving an alternator, which powers the electrical power system (EPS) of the UAS. This paper presents a novel axial-flux machine-based motor-generator system (MGS), capable to operate as an engine starter thereby eliminating the external starter. The design is targeted to meet the specifications given in the US Army SBIR, to achieve a continuous power density of 3kW/kg for a 7kW power rating. Additionally, the design also meets the dimensional requirements, required to fit with the existing engine. The compact power converter design and control also compliment the motor-generator design. The necessary design steps, and control algorithm to support bidirectional flow are discussed in detail. Finally, detailed simulation results verifying the performance requirement during engine start, generation mode, and emergency mode are also presented.